Transient global amnesia in legal proceedings - Griebe, Martin; Bäzner, Hansjörg; Kablau, Micha; Hennerici, Michael G.; Szabo, Kristina (International journal of legal medicine, 2015)
Transient global amnesia (TGA) is a neurological disorder characterized by an acute onset of severe anterograde amnesia. While retrograde amnesia may be present - although to a lesser extent - patients have no further cognitive disturbances or neurological signs. These symptoms resolve fully within several hours leaving a permanent memory gap for the duration of the episode and do not lead to long-term neurological deficits. In addition to well-defined clinical diagnostic criteria, in up to 80 % of patients, small, point-shaped lesions in the hippocampus are detected 24-48 h after symptom onset on diffusion-weighted magnetic resonance images. Despite several etiological hypotheses, to date, there is no scientific proof for the etiology of TGA or the small hippocampal lesions. Interestingly, in a large number of cases, an emotionally or physically straining event precipitates the onset of TGA, suggesting a stress-related mechanism. We report two cases of TGA occurring in legally relevant settings: affecting the victim of brutal burglary and the key witness in a murder trial. In the context of forensic medicine, the knowledge of this disorder and recognition of its typical features are essential.